Do Institutions and Culture Matter for Business Cycles? - Sumru Altug; Fabio Canova (Koç University-TÜSİAD Economic Research Forum (ERF), 2012)
We examine the relationship between institutions, culture and cyclical fluctuations for a sample of 45 European, Middle Eastern and North African countries. Better governance is associated with shorter and less severe contractions and milder expansions. Certain cultural traits, such as lack of acceptance of power distance and individualism, are also linked business cycle features. Business cycle synchronization is tightly related to similarities in the institutional environment. Mediterranean countries conform to these general tendencies.
Keywords: C32; E32; 330; Business cycles; institutions; culture; Mediterranean countries; synchronization; Konjunkturzusammenhang; Institutionelle Infrastruktur; Nationalkultur; Systemvergleich; Europa; Mittlerer Osten; Nordafrika